THE WEEKEND TOUR AS THE PROSPECTIVE TREND OF RURAL DEVELOPMENT - О. В. Чайковська; О. В. Чайковський (Подільський вісник: сільське господарство, техніка, економіка)
Currently, the development of domestic tourism in Ukraine has now been officially recognized as a strategic priority. Statistics show that in many foreign countries, revenues from domestic tourism make up to 80% out of the total tourism type. Local tourism enhances domestic consumption and, as a result, it creates demand for local goods and services. Domestic tourism contributes to the development of related industries, even those considered unprofitable. The development of domestic tourism can become a source of financial income for the country’s economic system and stabilize the labour market. Therefore, the state and prospects of the development of the domestic tourism, the weekend tour, in particular, as a direction that will contribute to the development of rural areas in different regions of Ukraine, require detailed research. Khmelnytskyi region has prerequisites for the development of a weekend tour, namely: beautiful landscapes, unique flora and fauna, the presence of rivers, lakes and forests, protected areas, rich architectural heritage, low price for tourist services. In addition, there is a large number of tour operators in the region, developed infrastructure and repaired roads even in remote villages. The purpose of our article is to analyze the development of weekend tours as the prospective trend of domestic tourism development in the Khmelnytskyi region. The regional features of the development of weekend tours in Ukraine, in the Khmelnytskyi region, in particular, are revealed. An analysis of the level of implementation of weekend tours in the region is carried out. Recommendations for improving the organization of weekend tours in the Khmelnytskyi region have been developed. The authors of the article are convinced that the study and adopting the best practices of European countries in the context of a weekend tour will contribute to an increase in income from domestic tourism.